PENGEMBANGAN STRATEGI PEMASARAN PRODUK OLAHAN SUSU “KOMIKU” PADA MERRY FOODIES LOMBOK TIMUR - Ni Nyoman Suli Asmara Yanti (Waisya : Jurnal Ekonomi Hindu, 2022)
Milk is a food that is rich in benefits and nutrients. There are many benefits obtained from the content of milk, making milk produced by many producers. One of the home industries that produces dairy products is Merry Foodies, which is located in Selong, East Lombok Regency, West Nusa Tenggara Province. The business idea of ​​making Komiku dairy products originated from the phenomenon of public interest, especially the Indonesian people who are interested in things that are related to the South Korean state, including processed food products that are often shown on South Korean television shows. In this study, we will discuss how to develop a marketing strategy for "Komiku" dairy products at Merry Foodies, East Lombok with a qualitative research approach. The analysis used in this research is SWOT analysis . The results on the SWOT matrix show that Merry Foodies as a milk processing producer has strengths in terms of packaging, taste, raw materials, and prices. However, there are several weaknesses, namely products that are easily damaged, difficulties in terms of distribution to more remote areas, limited capital and the absence of BPOM. Opportunities owned are quite broad market share, large target market and product diversification. Meanwhile, the threats they have are the season, the nature of consumers and new competitors. The development of the marketing strategy used by Merry Foodies is the convert selling strategy and other strategies in the marketing mix.